Too Big, Will Fail. Megaevents and Protest Participation - Massidda, Luca; Parisi, Stefania (PARTECIPAZIONE E CONFLITTO, 2017)
The paper examines the relationship between “social democratic megaevents” (Olympic Games and World Expos) and political protests. It tries to analyze the reasons that led these popular ceremonies to act in our societies as catalysts of social conflict and activators of an “agonistic citizenship”. Today some structural characteristics of the network society – growth of urban populations; increase in migration flows; widening of socioeconomic disparities – determined a renewed “political” interest for these great public rituals, which in a previous season of the modernity had shown themselves capable to patch up the lacerations of the social fabric. But in recent years something is broken in the relationship between megaevents and urban populations and we are witnessing a growing antagonism against events histori-cally conceived with a function of social “glue”. The aim is therefore to reflect on the meaning of this “an-tagonistic drift” of “social democratic mega-events” through the analysis of a specific case study: the Atti-tudine NoExpo Network (Milan 2015). We identified four crucial dimensions to trace the NoExpo move-ment’s physiognomy and define the reasons for its opposition to the world fair: the historical relation be-tween Milan and a cultural form of antagonism; the crucial role of the territorial factor in the formation and evolution of the movement; the centrality of the practices in the structuring of the movement’s iden-tity; the adoption of an instrumental and tactical approach in the choice and use of media